Influence of Heme Oxygenase-1 on Rats with Diabetic Retinopathy Through ERK1/2 Signaling Pathway: HO-1 effects on ERK1/2 Signaling Pathway - Huo, Jie; Meng, Gaoqiang; Jiang, Xuguang (Cellular and Molecular Biology, 2022)
The study aimed to investigate the influence of heme oxygenase-1 (HO-1) on rats with diabetic retinopathy (DR) through the extracellular signal-regulated kinase (ERK) 1/2 signaling pathway. 40 rats were selected and divided into Control group (n=10), diabetes mellitus (DM) group (n=10), cobalt protoporphyrin (CoPP) group (n=10) and zinc protoporphyrin (ZnPP) group (n=10) according to weight. Streptozotocin (STZ) was intraperitoneally injected to establish the DM model in DM, CoPP and ZnPP groups, and CoPP and ZnPP solution was intraperitoneally injected in CoPP and ZnPP groups, respectively. Blood was drawn to determine fasting blood glucose. The changes in the protein and messenger ribonucleic acid (mRNA) levels were evaluated via Western blotting and polymerase chain reaction (qRT-PCR), respectively. Enzyme-linked immunosorbent assay (ELISA) was performed to measure antioxidant capacity and the levels of total reactive oxygen species (ROS), malondialdehyde (MDA), glutathione (GSH) and glutathione peroxidase (GPx). The weight of rats was notably higher in the CoPP group and lower inZnPP group than in the DM group (p<0.05). After induction of DM, compared with those in the DM group, the protein expression levels of Nrf2 and pERK were considerably elevated in the CoPP group (p<0.05) but declined remarkably in the ZnPP group (p<0.05). The levels of total ROS and MDA were notably elevated (p<0.05) in DM and ZnPP groups, with a lowered level of GPx and distinctly elevated levels of MDA and total ROS (p<0.05). Moreover, the mRNA expression level of HO-1 in the retinas of rats was remarkably raised in the DM group and CoPP group (p<0.05), but it declined markedly in the ZnPP group (p<0.05). The red fluorescent aggregation of Nrf2 and pERK proteins was overtly less in the ZnPP group than that in the DM group (p<0.05). HO-1 can affect the level of oxidative stress and intervene in retinopathy in DM rats through the Nrf2/ERK pathway.